The Effect of Gender Gap in Education, Wages and Employment on Human Development Gender Based in Indonesia - Latiffa Aurelien Putri; Ambya, Ambya; Arif Darmawan (Cita konsultindo, 2024)
The prevailing paradigm today emphasizes economic growth measured through human development rather than solely through per capita income. Enhancing welfare and improving the quality of life for communities are the ultimate goals of economic development. Achieving these objectives requires substantial efforts that avoid bias related to gender, ethnicity, race, religion, and class. However, in practice, these efforts often overlook issues of equality and justice, reflected in the differing roles of men and women as both agents and beneficiaries of development. This study aims to investigate the impact of average years of schooling, average wages, and labor force participation rates on the Gender Development Index across 34 provinces in Indonesia from 2013 to 2022. The analysis methods employed include model fit testing, classical assumption testing, panel data linear regression, partial (t-test) and simultaneous (F-test) hypothesis testing, as well as coefficient determination using Eviews. The findings reveal that average years of schooling and average wages have a positive and significant effect on the Gender Development Index, while labor force participation rates do not significantly impact the Gender Development Index.